Facilitating pura medicina: Finnish mystical tourism and religious appropriation - Heinonen, Tero (Approaching Religion, 2023)
In this article, based on my doctoral research, I discuss the appropriation of religious elements from South America by Finnish ‘mystical tourists’. The plant medicine ceremonies are approached as spiritual commodities. Imagining local beliefs and practices as ancient cultural heritage, essentially and authentically spiritual, Finnish mystical tourists adapt these practices for their own therapeutic uses. They are accompanied by singing prayers to various plant spirits. Among the appropriated elements are the ceremonial ingestion of imported organic cacao, sacred tobacco and ayahuasca, as well as praying by singing to plant spirits understood in terms of animism. My findings indicate how the appropriated cultural elements are given therapeutic functions in collectively created musical and ritual spaces for individual well-being. I analyse appropriation in categories introduced by Richard A. Rogers (2006) and understand the ceremonies to provide ‘mystical tourists’ with a role as a racially privileged group over the subaltern indigenous peoples through processes of commercialization, where reimagined cultural elements become spiritual commodities to be bought and sold in commercial networks on the basis of access. I argue that the associated forms of cultural appropriation align with the individualistic spiritual well-being needs of the Finnish participants and are related to the theme of ‘sacralization of the self’.